Nightmare obscura : a dream engineer's guide through the sleeping mind - Carr, Michelle (Henry Holt and Company, 2025)
"A leading sleep expert reveals the latest science behind the dreaming brain and why we have nightmares-offering key insights into how harnessing dreams can improve your sleep and health. To most, dreams are things that slip away when you reemerge into the waking world, their remnants jumbled up and only half recalled. At their best, they are populated by pleasant recollections and surreal experiences. But at their worst, they can be traumatizing and prevent us from receiving the necessary benefits of sleep. So why do we dream at all? What makes a person prone to nightmares? How do our bodies interface with our brains when we're not awake? And how can we harness our sleeping minds to improve our waking lives? In Nightmare Obscura, dream researcher Michelle Carr unlocks the science behind the sleeping body, exploring the relationship between dreams and mental health, with a deep dive into the neuroscience behind some of the most interesting aspects of dreaming: nightmares, lucid dreams, and the cutting-edge field of dream engineering." --